A consumer's case for regulating electronic credit and debit transfers in South Africa. (2018) - Papadopoulos, Sylvia
The OECD urges regulators to strengthen consumer protection for users of electronic payment systems, by ensuring that there are minimum levels of payment protection and that the protection applies uniformly. South Africa does not have dedicated legislation for electronic payments like the European Union's Payment Services Directives. The consequence is that the consumer carries a disproportionate amount of risk and when they resort to litigation it does not produce consistent results. The primary aim of this paper is to elucidate on the problems faced by these consumers through a short synapsis of South African court decisions. This position is in sharp contrast to the EU where among others the PSD2 aims to make payments more secure and to protect consumers. This paper's secondary aim is to explain how the EU is addressing the issues of refund rights for consumers, the rights and duties of consumers and payment institutions alike within the electronic payments arena.